Analisis Tekanan Keluarga terhadap Mental Health Mahasiswa Akhir - Rahman, Surya; Wirtati, Ira (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to analyze family pressure on the mental health of final year students, then discuss how family pressure affects the mental health of final year students, and how to effectively deal with family pressure on the mental health of final year students. This study uses a qualitative method with a case study type. The data collection techniques used are (1) direct observation of family pressure on the mental health of final year students, (2) interviews with 3 informants, namely final year students in semesters IX, XII, and XIII in the Islamic Counseling Study Program, Faculty of Da'wah and Communication, State Islamic University of North Sumatra, Medan. (3) documentation study through literature and references relevant to the research focus. The findings of this study indicate that students who have good and communicative relationships with their families tend to be able to cope with pressure more stably. The emotional support provided by families in the form of motivation, understanding, and physical presence has been proven to help students maintain their mental health. This means that family pressure does not always have a negative impact if it is conveyed in the right way and accompanied by strong moral support. Therefore, it is important for families to understand that the final phase of college is a stressful time for students, and the right support greatly influences their academic success and mental stability.